Seroprevalence of Brucella spp and related risk factors in cattles from Laghouat district, South Algeria (VETERINARIA, 2023)
Brucellosis of cattle is endemic in Africa, including Algeria, and various studies have revealed a wide range of seroprevalences. The study’s aims were to assess the prevalence of Brucella spp using the ELISA test and to evaluate the related risk factors in cattle. A cross-sectional study was performed on 1393 cattle from the Laghouat area. An organized questionnaire was used to gather a wide range of animal information (age, gender, breed, husbandry system and geographic location). The obtained seroprevalence was 6.2% (95% CI: 5.1-6.7). Risk factors were evaluated using univariate analysis, at 5% level of significance (i.e. p
Keywords: Brucellosis of cattle; Laghouat area (Algeria); seroprevalence; risk factors